Iron mineralogy and speciation of sediment iron-bearing minerals in mangrove forest: Case study of Zhangjiang estuary, China. (February 2020) - Yang, Dan; Liu, Jingchun; Zhao, Weiwei; Huang, Qi; Xue, Liyang; Yan, Chongling; Lu, Haoliang
Abstract: Few investigations of iron speciation exist in intertidal conditions with little attention given to understanding the geochemical behavior of Fe 3+ –Fe 2+ and its biogeochemical processes. Here, one sediment core was collected in Yunxiao mangrove forests, Zhangjiang estuary, China and iron mineralogy was determined by magnetic methods and Mössbauer spectroscopy. Changes in magnetic susceptibility, susceptibility of anhysteretic remanent magnetization, and saturation isothermal remanent magnetization were linked to changes of pseudo-single domain soft coercive components with minor antiferromagnetic fractions and the presence of minimal concentrations of superparamagnetic particles was confirmed by the no frequency dependent of AC magnetization. A positive correlation between L-ratio and hard isothermal remanent magnetization is congruent with the distribution of high-coercivity antiferromagnetic minerals. At 295 K, the Mössbauer spectrum of specimens was well fitted with a single magnetic sextet, hematite and two magnetic doublets, paramagnetic Fe 2+ and paramagnetic Fe 3+ . The usefulness of magnetic data and Mössbauer spectroscopy could offer valuable analytical tools for tracking changes of iron speciation and phase in the intertidal conditions. Highlights: The abundance of core χLF was 21.97–26.63 × 10 − 8 m 3 kg − 1 . No clear tendency of χLF, SIRM, χARM and HIRM along with increasing depth was observed. Positive correlation was found between HIRM and Lratio .